Strategi dan Model Pengambilan Keputusan dalam Manajemen Pendidikan dalam Kajian Literatur Interdisipliner - Nurul Hayati; Syarif Hidayatulloh; Helma Putri Kusuma; Camelia Sabata; Komariyatul Hasanah; Mu’alimin Mu’alimin (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Making decisions is a crucial part of educational administration in order to successfully accomplish organizational objectives. Examining the idea and phases of decision-making in the management of teachers and other education staff is the goal of this study. A literature study is the approach taken, gathering information from books, journals, and related sources. According to the study's findings, making wise decisions requires a methodical process that includes problem identification, alternative analysis, choosing the best solution, execution, and evaluation. For decisions to be successful and responsible, ethics, dangers, and the interests of different parties must also be taken into account.